Bridging Spirituality and Ecology: An Analysis of the Rimbo Concept in Minangkabau Culture, Indonesia - Hidayat, Thaufiq; Iqbal, Imam; Hamzah, Vikri; Hidayat , Thaufiq (Journal of Malay Islamic Studies, 2025)
Today's global ecological crisis demands an interdisciplinary approach that relies not only on technology and policy but also on spiritual values ​​and local wisdom. This article explores the concept of rimbo in Minangkabau culture as a representation of the integrative relationship between spirituality and ecology. Rimbo, which means forest, in Minangkabau cosmology has a broader meaning as a sacred space that stores spiritual values, ecological ethics, and social rules based on customs. This study uses a qualitative approach with a phenomenological-hermeneutic method. Data were collected through a literature study of traditional manuscripts, interviews with local traditional figures and clerics, and participatory observation in the rimbo area. The study results show that rimbo is not only viewed as a natural resource but also as a cosmological entity inhabited by spiritual beings and protected through strict customary norms. Values ​​such as the prohibition of excessive exploitation, deliberation in management, and respect for the guardian spirits of nature show that rimbo bridges humans, nature, and the transcendent dimension. These findings indicate that integrating spirituality and ecology in the Rimbo concept can contribute significantly to the discourse of ecotheology and environmental conservation practices based on local culture. This study recommends a cross-cultural approach in building a new sustainability paradigm rooted in local spirituality and cosmology.